Quality of Social Relationships with Parents and Peers in Adolescents Born Extremely Preterm. Issue 3 (April 2023) - Taylor, H. Gerry; Hoskinson, Kristen R.; Vrantsidis, Daphne M.; Minich, Nori Mercuri; Busch, Tyler; Horn, Timothy; Mattson, Whitney I.; Nelson, Eric E.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: Adolescents born extremely preterm (EPT, gestational age [GA] <28 weeks) are at higher risk for problems in peer socialization than those born full-term (FT, GA >36 weeks). This study was designed to examine the possibility that adolescents born EPT may also have difficulty in transitioning from parents to peers for socialization, a process referred to as "social reorienting." A secondary aim was to investigate associations of social reorienting with other neurodevelopmental characteristics. Methods: The Network of Relationships Inventory, Relationship Quality Version was administered to 24 adolescents (ages 11–16 years) born EPT and 29 born FT to obtain self-ratings of closeness and discord with parents and peers. Measures of other neurodevelopmental characteristics included tests of cognitive and social skills, adolescent self-ratings of adjustment and victimization, and parent ratings of youth behavior and adaptive skills. Mixed model analyses controlling for sex, socioeconomic status, and race were conducted to examine group differences in measures of relationship quality and their associations with other neurodevelopmental characteristics. Results: The EPT group had higher ratings of closeness with parents than the FT group. For adolescents from lower socioeconomic backgrounds, those born EPT had lower closeness with peers. Higher closeness with parents was associated with lower test scores. Lower closeness and more discord with peers were associated with more behavior problems. Conclusion: Findings suggest that adolescents born EPT have difficulties in social reorientation toward peers and identify factors related to these difficulties. Results imply a need for interventions to improve peer socialization in youth born EPT.